2017
DOI: 10.1017/s1092852917000219
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of dopaminergic therapies in Parkinson’s disease: shedding light on aberrant salience

Abstract: Psychotic subjects and patients with Parkinson's disease (PD) "on" dopaminergic drugs, especially on dopamine agonists, present a hyperdopaminergic state that interferes with learning processing. These clinical populations present with distinct alterations of learning that share an increased potential motivational significance of stimuli: psychotic subjects may attribute salience to neutral stimuli, while medicated PD patients may overvalue rewards. Herein is discussed the speculative hypothesis that the hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These discussions clarify that entropic processing itself is of neutral valence and is not predictive of long-term outcomes. Additionally, we will describe how an entropic processing style can be arrived at through a variety of neurobiological states by discussing overlap with other psychosis-like experiences that are largely neurobiologically distinct from the effects of classic psychedelics, including those produced by excessive dopamine (DA) signaling (Poletti, 2018). The role of alterations in thalamic connectivity in potentially provoking a sense of increased information richness will also be explored due to this being a frequent point of comparison.…”
Section: Entropic Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…These discussions clarify that entropic processing itself is of neutral valence and is not predictive of long-term outcomes. Additionally, we will describe how an entropic processing style can be arrived at through a variety of neurobiological states by discussing overlap with other psychosis-like experiences that are largely neurobiologically distinct from the effects of classic psychedelics, including those produced by excessive dopamine (DA) signaling (Poletti, 2018). The role of alterations in thalamic connectivity in potentially provoking a sense of increased information richness will also be explored due to this being a frequent point of comparison.…”
Section: Entropic Processingmentioning
confidence: 99%
“…Additionally, studies in individuals without psychosis suggest that altered salience can stem from increases in DA signaling. L-DOPA use in Parkinson's disease patients can increase the experience of aberrant salience (Cicero et al, 2010) compared with drugnaıve Parkinson's patients (Poletti et al, 2014;Poletti, 2018). This has been posited to be due to excessive DA signaling within the ventral striatum, leading to altered reward prediction encoding (Glimcher, 2011;Boehme et al, 2015), similar to that of psychosis patients (Poletti, 2018).…”
Section: B Altered Saliencementioning
confidence: 99%
See 1 more Smart Citation
“…24 We developed the model predicated on the well-established relationship between dopamine, either endogenous or exogenous, and psychosis across the diagnostic spectrum from bipolar disorder and schizophrenia to Parkinson's disease to AD, in which D1/D3 dopamine receptor genetic variations and D2/D3 receptor density in the striatum have been directly correlated with psychotic symptoms in AD patients. [25][26][27][28][29][30] Previously, we reported that the P301L/COMT-model evidences increased extracellular dopamine and surges in frontal tau phosphorylation from extracellular dopamine in response to catecholamine reuptake inhibition. 24 Tau phosphorylation patterns in the absence of absence of pharmacologic treatment and behavioral deficits with relevance to psychosis in the P301L/COMT-model such as sensorimotor gating abnormalities in the form of PPI and locomotive phenotypes have not been previously reported.…”
Section: Introductionmentioning
confidence: 98%
“…We have developed a newer candidate specifically to model outcomes relevant to AD psychosis comprising a P301L tau mutation together with a deleted dopamine‐degrading catechol‐ O ‐methyltransferase (COMT) gene (COMTKO) 24 . We developed the model predicated on the well‐established relationship between dopamine, either endogenous or exogenous, and psychosis across the diagnostic spectrum from bipolar disorder and schizophrenia to Parkinson's disease to AD, in which D1/D3 dopamine receptor genetic variations and D2/D3 receptor density in the striatum have been directly correlated with psychotic symptoms in AD patients 25–30 . Previously, we reported that the P301L/COMT– model evidences increased extracellular dopamine and surges in frontal tau phosphorylation from extracellular dopamine in response to catecholamine reuptake inhibition 24 .…”
Section: Introductionmentioning
confidence: 99%